Evaluating work placement supervisors’ ratings of Master’s in research psychology students at an open and distance e-learning institution in South Africa - Errolyn L. Gordon (Journal of Teaching and Learning for Graduate Employability)
This paper examines the dataset of work placement supervisors’ feedback from 2014 to 2017 on the skillset of Master in Research Psychology students during their first and second placement periods. A total of 47 placement feedback reports were analysed. The analysis included frequency counts and qualitative content analysis using Microsoft (MS) Excel software. The study reveals that placement supervisors place significant value on soft skills, notably a willingness to learn, and frequently rate students favourably on interpersonal skills. The results highlight the importance of viewing placement supervisors as co-educational partners. By evaluating supervisors' ratings of research psychology students on work placement holds significant value in improving educational programs, enhancing student outcomes, aligning with employer expectations, and contributing to the broader understanding of work-integrated learning in research psychology. For students, it entails identifying areas of strength and areas for improvement in their performance. For the university program, this feedback can inform teaching and learning approaches by providing insights into the specific skills, competencies, and knowledge that students need to develop during their program. It can also help tailor feedback and support by understanding supervisors' feedback, leading to more effective guidance and constructive feedback for students. For the placement organisations, the research can contribute to supervisor training and development, ensuring they have the necessary skills to guide and evaluate students, while also improving work placement design and coordination to align with program learning outcomes and provide meaningful experiences for students.